Persistent Mullerian duct syndrome: Report of two cases with phenotypical immunohistochemical profiling. Issue 4 (November 2018) - Ambrosi, Francesca; Fiorentino, Michelangelo; Chessa, Francesco; Brunocilla, Eugenio; D'Errico, Antonietta; Bertuzzo, Rosa Valentina; Giunchi, Francesca
Introduction: Persistent Mullerian duct syndrome is a rare disorder of male organ development characterized by internal male pseudohermaphroditism. Persistent Mullerian duct syndrome is usually an incidental finding in patients presenting cryptorchidism, inguinal hernia, or a previous story of undescended testes. Case description: We report on two cases of persistent Mullerian duct syndrome: an adult fertile male with uterus and ectopic prostate occurring as pelvic mass and a 75-year-old organ donor with uterus and two fallopian tubes, discovered in course of organ recruitment. We performed routine histological analysis and immunohistochemical profiling of the different tissue components. Examined tissues were all benign, and the living patient is well after surgery. Conclusion: In order to prevent further complications such as infertility and potential malignant change, surgeons and surgical pathologists must be aware of this condition and should consider excision of the Mullerian remnant where possible.